answersLogoWhite

0

The idea is to simply replace x by its assumed value, 5. x + 6 = 5 + 6 = 11

The idea is to simply replace x by its assumed value, 5. x + 6 = 5 + 6 = 11

The idea is to simply replace x by its assumed value, 5. x + 6 = 5 + 6 = 11

The idea is to simply replace x by its assumed value, 5. x + 6 = 5 + 6 = 11

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
More answers

The idea is to simply replace x by its assumed value, 5. x + 6 = 5 + 6 = 11

User Avatar

Wiki User

15y ago
User Avatar

Add your answer:

Earn +20 pts
Q: If x equals 5 then what is x plus 6 equal to?
Write your answer...
Submit
Still have questions?
magnify glass
imp